Expanding Binomial Times Binomial

1.   Expand and simplify:

a)    (x + 5)(x - 3)                   b)    (2x - 1) (x + 4)                     c)    (1 - 3x) (2x + 7)                     d)     (3m + 2) (3m - 2)

Solutions to this question can be found at http://www.youtube.com/watch?v=IXIR_4LVzr8&list=UUm-Z_cRxySqM3GkXMKmDPUg&index=34&feature=plcp

Determining Whether a Relation is Linear, Quadratic or Neither Using a Table of Values

This video  http://www.youtube.com/watch?v=OCRoD0jZF7o&list=UUm-Z_cRxySqM3GkXMKmDPUg&index=36&feature=plcp  shows how to use a table of values, as well as first differences and second differences to determine whether a relation is linear, quadratic or neither.

Converting a Quadratic from Vertex Form to Standard Form

1.   Convert each of the Following from vertex form to standard form

a)    y = 2(x+1)^2 + 3                      b)   y = -4(x-3)^2 - 5

Solutions to this question can be found at http://www.youtube.com/watch?v=cE4Zb8MBfmE&list=UUm-Z_cRxySqM3GkXMKmDPUg&index=28&feature=plcp

Trinominal Factoring Where the Leading Coefficient is 1

1.   Factor each of the following trinomials:

a)   x^2 + 9x + 14                     b)   x^2 - 11x + 30                       c)    x^2 + 4x - 45                           d)   x^2 - x - 42

Solutions to these questions can be found at http://www.youtube.com/watch?v=zbdxMp3tFDw&list=UUm-Z_cRxySqM3GkXMKmDPUg&index=30&feature=plcp

Trinomial Factoring Where the Leading Coefficient is not 1 (i.e., common factor first)

1.    Factor each of the following trinomials:

a)   3x^2 + 18x + 27               b)   -2x^2 + 10x - 12                      c)   4x^2 + 4x - 288               d)   -x^2 + x + 2

Factoring to find the zeros of a parabola

1.   Find the zeros of each of the following parabolas:

a)   y = 2x^2+4x-30                     b)   y = -5x^2 + 15x - 10                   c)   y = x^2 + 7x + 6

Factoring to find the zeros, finding the vertex, and graphing a parabola

1.   For each of the following, find the zeros, find the vertex, and graph the parabola using that information

a)  y = 2x^2 + 4x - 6               b)  y = -3x^2 - 6x               c)  y = -x^2 - 8x - 15